Is echocardiography necessary for all single umbilical artery fetuses? A retrospective study in a selected Chinese population. Issue 4 (15th January 2019) - Wang, Jian; Ye, Yujiao; Xin, Tiantian; Zhang, Xi; Chen, Sun; Wu, Yurong; Sun, Kun
Abstract: Aim: Previous evidence on the relationship between single umbilical artery (SUA) and congenital heart disease (CHD) is controversial. We thus conducted a retrospective study to explore the potential risk factors associated with CHD in SUA fetuses, and verify if all these SUA fetuses should be referred for detail fetal echocardiography. Methods: We reviewed medical records of SUA fetuses referred to Xinhua Hospital for fetal echocardiography between September 2009 and February 2014. All the pregnancies were divided into two groups of CHD and non‐CHD according to the results of fetal echocardiography. The maternal and fetal characteristics were compared via χ 2 test and Fishers' test. Furthermore, Poisson regression was used to analyze the risk factors associated with CHD in SUA pregnancies. Results: Nineteen CHD cases (12.5%) were detected among 152 SUA fetuses, all with abnormal cardiac views during obstetric screening ultrasound ( P < 0.001). χ 2 test showed that abnormal cardiac screening findings, extracardiac abnormality and infection or threatened abortion during first trimester were significantly associated with prenatal detection of CHD ( P < 0.001). Multivariable Poisson regression after adjustment found that SUA fetuses with extracardiac abnormality had 4.74 (95% confidence interval: 1.89, 11.90) times higher risk of CHD. Conclusion: Incidence of CHD was higher in SUA cases, and CHD fetuses could be screened efficiently by abnormal cardiac screening during obstetric screening ultrasound. SUA fetuses with extracardiac abnormality and maternal risk factors have higher risk of CHD, and should be strongly recommended for fetal echocardiography. In contrast, SUA fetuses without above situations might only need routine obstetric follow‐up.